The Use of Information in Total Cost Management - Eldenburg, Leslie (The Accounting Review, 1994)
[In 1983, Medicare changed its method of reimbursement for hospitals from an all-charges-paid basis to a flat-fee-per-diagnosis basis. Managing the cost of treatment became increasingly important. In an effort to influence physicians to reduce the amount of resources used, hospital controllers began providing cost information about patient treatment to physicians. Several questions were being asked at the time: (1) Although society affirmed that cost containment is necessary, should physicians ethically consider costs in making treatment decisions? (2) Would a group of professionals incorporate a new set of information provided by the accounting system into their decision-making process? (3) What design of management accounting system would best facilitate physician decision making around cost containment? This research examines the effects of providing cost reports, as a new information set, in this complex professional environment which is characterized by implicit contracts. An economic analysis explores the conditions necessary to align hospital and physician goals around cost management. An appropriate set of accounting information may help detect overtreatment. In addition, the reputation cost of being known as an overtreater may provide the necessary incentive for success in containing costs. A cross-sectional analysis of hospitals was undertaken to determine the response of physicians to this new information set. Differences in their practice patterns were analyzed in relation to the types of accounting information received. Average charges were used to measure practice patterns. The study population was partitioned according to the types of information provided and frequency of reporting. The results of the empirical analysis suggest hospitals providing physicians with their own case costs and some comparison information had significantly lower average charges, statistically, than those hospitals that did not. The comparison information may be reports of other individual physicians' case costs or on-the-average practice patterns within the hospital or within the state. This study contributes to current research in several ways. First, a theoretical framework has been developed that links incentives to manage costs with the type of accounting information provided in organizational environments characterized by a reliance upon implicit contracts. Second, from an accounting perspective, disaggregate information gathered by the accounting process and some sort of benchmark are necessary to induce this reputation effect that appears to influence behavior. Third, a linkage between total cost management and the use of accounting benchmark information in an implicit contracting environment is documented.]